Effect of Waste Tire Rubber Particles on the Properties of Rubberized Concrete - Hasan, Abu; Ahmed, Shameem; Ahsan, Raquib (Civil Engineering Journal, 2025)
Millions of waste tires accumulate annually worldwide, posing environmental and public health challenges. Recycling these tires in concrete production presents a sustainable and practical solution. The present study was intended to investigate the effects of waste tire particles of varying sizes and shapes; specifically granular, short fiber, and mixed fine crumb rubber, along with coarse shredded rubber; on the characteristics of rubberized concrete. Fine rubber particles replaced sand, while shredded rubber replaced stone aggregates at 5%, 10%, and 15% substitution levels by weight. Results revealed that increasing rubber content reduced density, compressive strength, modulus of elasticity, and tensile strength. However, workability, Poisson’s ratio, ductility, and toughness improved significantly in comparison with conventional concrete. This study compares the effects of particle size and shape of rubber used in rubberized concrete. Notably, the newly introduced short fiber-type rubber particles exhibited superior mechanical properties compared to the granular and shredded rubber forms, revealing their potential for structural applications.